Iran's foreign policy between non-alignment and strategic reset (geopolitical analysis) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The principle of non-alignment that was the basis of the Islamic Republic's foreign policy was replaced by efforts to create a bloc in partnership with traditional and rising Eastern powers. The Orientation Policy has yielded some benefits for Iran, but it has severely limited its foreign policy options, while its neighboring countries have been able to gain a wider margin of maneuver by balancing between East and West.In its recent economic policies designed to confront American hegemony, Iran is relying on strengthening its orientation to the East as a basic option to break American unilateralism in all economic fields. Hence, it has sought to join and obtain full membership in the Shanghai Cooperation Organization led by Russia and China, as well as joining the BRICS bloc.